Finite element analysis of the screw in percutaneous axial lumbosacral interbody fusion - Xu, Hong‐guang (Orthop Surg, 2010)
Objective:  To establish a three‐dimensional finite element model of the L(5)/S(1) motion segment with percutaneous axial lumbosacral screw and analyze the biomechanical stress on the screw. Methods:  With the help of related software and the Mechanical Virtual Human of China, a three‐dimensional finite element model was established. Three different loading conditions on the screw were analyzed with this model. Results:  Peak stresses on the screw under three loading conditions were 175.334 MPa, 183.765 MPa and 146.237 MPa, respectively. Generally, stress values were relatively low. The stress values were relatively high at the point of interbody fusion and middle part of the screw, all the highest values being localized to the upper and lower threads closest to the middle part. Comparison among the three conditions showed that torque load was the greatest, followed by vertical load, with lateral bending being the least. Conclusion:  Percutaneous axial lumbosacral screw easily meets normal loading conditions and may be an effective method for lumbosacral fusion.